Design and implementation of solar powered stirling engines: Review - Vasu R.; Ismail F.B. (American Institute of Physics Inc., 2023)
Growing energy consumption leads to discovery of new technology to accommodate global energy demand. Stirling Engine is one of the traditional engine which can harvest solar energy with minimal modification on the configuration. This paper covers literature review on Solar Powered Stirling Engine technology. The development of traditional Stirling Engine will be discussed on earlier part. The second part covers the integration of solar power with Stirling Engine and application of this combined system in industry. There were many researches and studies carried out previously on the development and application of traditional Stirling Engine and solar powered Stirling Engine. This paper is focus on optimization of performance of Solar Powered Stirling which will provide comprehensive details on the factor needed to be optimized in order to develop all rounded Solar Stirling Engine for future studies. 2018 Author(s).